ANALISIS KEBUTUHAN MAHASISWA DALAM PENERAPAN MULTIMEDIA INTERAKTIF PADA CABANG OLAHRAGA FUTSAL DI STKIP KUSUMANEGARA - Iqbal, Muhammad (INSPIREE: Indonesian Sport Innovation Review, 2020)
The purpose of the study. To find out the needs of interactive multimedia in students. And based on field observations that there is a lack of understanding and effective application of basic techniques in futsal. Therefore the application of interactive multimedia is used as learning in practice. Materials and methods. Initial design Development of basic training techniques based on the results of literature studies and needs analysis. The needs analysis was carried out with the subject of 35 students who had passed the futsal course. The steps used in the development of basic futsal training techniques include; product, technical implementation of limited trials, revisions, wider trials, revision of the final product, dissemination and implementation. Results. The results of the analysis show that 100% of students have played futsal, 80% have participated in futsal training, 45% know the variations of training in futsal, 91% like to practice with different training variations, 100% require the development of variations in futsal training, and 97% want a variety of exercises. futsal is made in the form of interactive media. The results of small group trials with a percentage of 91.69% in good categories and for the results of large group trials with a percentage of 94.16% with good categories. Conclusions. Interactive media products can be used in actual practice.